RANCANGAN SISTEM INFORMASI PENANGANAN KELUHAN PENGGUNA PT XYZ - Verawaty Situmorang (LP2MTBM MAKARIOZ, 2019)
Digest— PT XYZ's Information Technology (IT) Division is a division that supports the development and management of information systems needed in the business of the company PT XYZ. One application built by the IT division of PT XYZ is an application that is used to manage information on PT XYZ Marketing and Sales products. At present the use of applications often complains from users, among others, the incompatibility of information displayed with reality in the field, complaints about technical problems where there are errors when using the application, and so forth. Complaints most often occur when an update or new feature or function is added to the application. Handling of user complaints is considered not handled properly, therefore the E-Ticket application development project is proposed to assist in handling user complaints. Complaints are sent by telephone, email or by directly conveying the problem. The cause of the problem can be a database error, application malfunction, network problems and so on. In this study an analysis of the system requirements was described using use case diagrams and ER diagrams and continued by doing the design so that in the end the results of this study were a draft application for PT XYZ User Complaints Handling